2016
DOI: 10.1016/j.berh.2016.10.012
|View full text |Cite
|
Sign up to set email alerts
|

The role of psychological factors in inflammatory rheumatic diseases: From burden to tailored treatment

Abstract: a b s t r a c tInflammatory rheumatic diseases have a long-lasting effect on patients' physical and psychological functioning, for instance, due to disabling symptoms and unpredictable disease course. Consequently, many patients show adjustment problems such as depressed mood, which in turn can negatively influence their disease outcome. Specific biopsychosocial factors have shown to affect this outcome. For example, daily stress, cognitive-behavioral risk factors such as pain catastrophizing and avoidance, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 90 publications
1
21
0
1
Order By: Relevance
“…However those at risk need to be identified and intervention measures introduced as early as possible (7,11), as impact on behaviour and management of disease can still be profound. Therefore regular screening/discussions to assess the psychosocial burden impacting quality of life is important to personalise treatment (28). It is imperative to match the needs and preferences of the young person with the support provided (26), with HCPs providing a flexible and youth-friendly approach.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However those at risk need to be identified and intervention measures introduced as early as possible (7,11), as impact on behaviour and management of disease can still be profound. Therefore regular screening/discussions to assess the psychosocial burden impacting quality of life is important to personalise treatment (28). It is imperative to match the needs and preferences of the young person with the support provided (26), with HCPs providing a flexible and youth-friendly approach.…”
Section: Discussionmentioning
confidence: 99%
“…They can increase optimism and alleviate feelings of social isolation, which can assist the adoption of healthy behaviours, disease management skills (25), and acceptance of help with disease management (27). Conversely problematic unsupportive relationships lead to increased distress and disease activity (26,28), by being oppressive, underestimating the disease and not providing useful advice (29). Regardless of social network size, AYA primarily disclose their illness to family members and only to a few peers.…”
Section: The Importance Of Peer Support For Aya With Rmdmentioning
confidence: 99%
“…In line with this view, most studies of patients with chronic pain have reported an association between acute stressors and increased pain and physical disability (Andersson, 1999;Sturgeon, Finan, & Zautra, 2016;Van Middendorp, Lumley, Jacobs, Bijlsma, & Geenen, 2010). Also, many studies have provided evidence for a pain-augmenting association of stress and stress-vulnerability factors, such as neuroticism and a tendency to worry (Al-Allaf et al, 2002;Andersson, 1999;Davis, Luecken, & Zautra, 2005;Evers, Verhoeven, et al, 2014;Evers, Zautra, & Thieme, 2011;Geenen et al, 2006;Low & Schweinhardt, 2012;Nicol et al, 2016;Ortego et al, 2016;Raphael, Widom, & Lange, 2001;Van Middendorp & Evers, 2016). Intriguingly, a number of studies has revealed that major stressors might be associated with the development of chronic pain.…”
Section: Stress and Chronic Painmentioning
confidence: 93%
“…Because stress is part of life and cannot always be prevented, measuring stress-vulnerability factors (p.182) can also be useful in order to identify individuals at risk. For example, investigators may screen for neuroticism, hyper-vigilance, worrying, fearavoidance, and catastrophizing (Evers, Kraaimaat, Geenen, Jacobs, & Bijlsma, 2003;Evers, Gieler, Hasenbring, & Van Middendorp, 2014;Van Middendorp & Evers, 2016 To gain insight into the number, severity, and consequences of daily stressors, ecological momentary assessment (EMA) procedures can be used to measure acute stress (and potential consequences such as pain) levels by means of (electronic) diaries over a specific period of time, varying from several days up to a year (McIntyre et al, 2016;Shiffman, Stone, & Hufford, 2008). Technological advances such as EMA allow investigators to gauge specific thoughts, actions, and emotions that might provide detailed insight into the stress experience and its consequences.…”
Section: Stress Assessmentmentioning
confidence: 99%
“…1 This affection includes the combination of anxiety, depression, and participation in daily living activities. It can be thought that individuals can be affected from different diseases in different ways.…”
mentioning
confidence: 99%